Organic Solvent Effects in Biomass Conversion Reactions - Shuai, Li; Luterbacher, Jeremy (ChemSusChem, 2016)
Transforming lignocellulosic biomass into fuels and chemicals has been intensely studied in recent years. A large amount of work has been dedicated to finding suitable solvent systems, which can improve the transformation of biomass into value‐added chemicals. These efforts have been undertaken based on numerous research results that have shown that organic solvents can improve both conversion and selectivity of biomass to platform molecules. We present an overview of these organic solvent effects, which are harnessed in biomass conversion processes, including conversion of biomass to sugars, conversion of sugars to furanic compounds, and production of lignin monomers. A special emphasis is placed on comparing the solvent effects on conversion and product selectivity in water with those in organic solvents while discussing the origins of the differences that arise. We have categorized results as benefiting from two major types of effects: solvent effects on solubility of biomass components including cellulose and lignin and solvent effects on chemical thermodynamics including those affecting reactants, intermediates, products, and/or catalysts. Finally, the challenges of using organic solvents in industrial processes are discussed from the perspective of solvent cost, solvent stability, and solvent safety. We suggest that a holistic view of solvent effects, the mechanistic elucidation of these effects, and the careful consideration of the challenges associated with solvent use could assist researchers in choosing and designing improved solvent systems for targeted biomass conversion processes. Solvents, how art thou interfering? Biomass‐derived molecules are an attractive resource for the production of renewable fuels and chemicals. However, producing intermediates at high yields and rates has been a major challenge to biorefinery development. Organic solvent effects can dramatically improve conversion rates and product selectivities by influencing solubility or thermodynamics of biomass components. Herein, these effects are discussed.